(untitled) (Research, Society and Development, 2023)
The study has as its theme low adherence of women to the cytopathological exam: an experience report, which was carried out through a situation observed in the Basic Health Unit (UBS), located in the municipality of Irecê-Ba, through the implementation of the Strategic Planning Situational, lasting from August to December 2022, it aims to: Increase women’s adherence to cytopathological examination at UBS in Irecê-BA. This is an experience report, descriptive, with a qualitative approach, the collection in the database occurred via VHL using the Boolean operator “AND”, with the following Descriptors in Health Sciences: Cytopathological examination; Cervical cancer; preventive, articles used as a basis are from the last five years. The results show the low adherence to the cytopathological test by women, which is linked to women’s perception and factors such as low income, education and religion, in addition to the need for the UBS team to capture these users and understand the factors of non-performance, in addition to training of professionals and humanization in order to offer a qualified and humanistic service. It is concluded that low knowledge on the part of women and greater proximity of primary care with users.